Readiness to monitoring as a pedagogical problem (Pedagogy of Higher and Secondary Education, 2014)
Kukharuk O. V. Readiness to monitoring as a pedagogical problem.The article deals with the problem of future teachers to monitor. Conducted thorough research of the main approaches to defining the essence of the concept of «readiness» based on analysis of psychological and educational literature. The essence of the concept of «readiness for monitoring». Allocated and describes the six interrelated structural components readiness monitoring: motivational, scientific-theoretical, cognitive, evaluative, psychological and praksykolohichnyy.
Keywords: readiness; readiness for monitoring; motivation; scientific-theoretical; cognitive; evaluative; praksykolohichnyy and psychological components